2007
DOI: 10.2298/jsc0712403m
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the morphology and electrocatalytic properties of electrochemically formed Ag/TiO2 composite deposits on titanium surfaces

Abstract: Three different forms of Ag/TiO 2 composite layers, which have whisker-, dot-and island-like distribution of silver were obtained on a mechanically polished titanium surface by adjusting the conditions of silver deposition from an aqueous AgNO 3 solution. The deposit morphology was the result of both the program of electrode polarization and the template action of the simultaneously formed TiO 2 layer. The catalytic activity of the composite layers toward the oxygen reduction reaction was studied in aqueous 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…[86] Ag/TiO 2 composite showed the ORR activity to be between bulk Ag and TiO 2 , whereas the activity increased with increasing Ag content. [87,88] Tafel slope values of À84 mV dec À1 and À100 mV dec À1 were reported on these composites, which were between that of bulk Ag and pure TiO 2. [87,88] Higher ORR activity of Ag-Mn 3 O 4 /C catalysts as compared to Ag/C has been demonstrated.…”
Section: Orr On Ag Catalysts Deposited On Composite Supportsmentioning
confidence: 75%
See 2 more Smart Citations
“…[86] Ag/TiO 2 composite showed the ORR activity to be between bulk Ag and TiO 2 , whereas the activity increased with increasing Ag content. [87,88] Tafel slope values of À84 mV dec À1 and À100 mV dec À1 were reported on these composites, which were between that of bulk Ag and pure TiO 2. [87,88] Higher ORR activity of Ag-Mn 3 O 4 /C catalysts as compared to Ag/C has been demonstrated.…”
Section: Orr On Ag Catalysts Deposited On Composite Supportsmentioning
confidence: 75%
“…[87,88] Tafel slope values of À84 mV dec À1 and À100 mV dec À1 were reported on these composites, which were between that of bulk Ag and pure TiO 2. [87,88] Higher ORR activity of Ag-Mn 3 O 4 /C catalysts as compared to Ag/C has been demonstrated. [89] As Tafel slopes of these catalysts were similar, it was concluded that the active sites for O 2 reduction are on silver, not on Mn 3 O 4 .…”
Section: Orr On Ag Catalysts Deposited On Composite Supportsmentioning
confidence: 75%
See 1 more Smart Citation
“…It can be seen that the EG composite electrode containing Romanian zeolite with small amount of Ag + cations distributed randomly in the zeolite structure displays complex behaviour with several electrochemically distinct species. The anodic part of the voltammogram is characterized by the occurrence of the anodic peaks corresponding to the electroformation of soluble [Ag(OH) 2 ] − complex species (the first peak, shoulder), to the electroformation of Ag 2 O (the second peak), and to the formation of AgO (the third peak) [16,17]. The cathodic part of the cyclic voltammograms is characterized by the occurrence of cathodic peaks corresponding to the electroreduction of AgO to Ag 2 O, the reduction of Ag + located in different sites of zeolite [12].…”
Section: Resultsmentioning
confidence: 99%
“…À complex species (first peak, shoulder), to the electroformation of Ag 2 O (second peak), and to the formation of AgO (third peak). The cathodic part of the cyclic voltammograms is characterized by the occurrence of cathodic peaks, corresponding to the electroreduction of AgO to Ag 2 O and Ag 2 O to Ag, respectively [22,23]. The presence of 4-CP increased all anodic peak currents corresponding to Ag oxidation being involved in oxidation processes.…”
Section: Voltammetric Measurementsmentioning
confidence: 99%